A study on the diversity in group and perceive group performance: A case study in Astro Television Network System Sdn Bhd / Najihah Ahmad Bkhtiar and Nur Elya Aina Mohd Ridzuan - Ahmad Bkhtiar, Najihah; Mohd Ridzuan, Nur Elya Aina (Faculty of Administrative Science and Policy Studies, 2013)
Diversity is often can be seen as one of the problems that happen in certain organization because of variety and difference of the employees either in term of the culture, demographic and knowledge. That’s why, it also may affect to perceive of employees performance especially when they are working in a groups. This research paper study on the diversity in group and perceive group performance in Astro Television Network System Sdn Bhd which located at Jalan Tun Razak, Kuala Lumpur. Since this research is the quantitative researchers therefore, for about 100 questionnaires been distributed to the staffs at Activation Departments and selected as the sample size for this research. For this research paper also, the researchers is actually want to identify the relationship of culture, demographic and knowledge diversity towards perceive of group performances especially at Activation Department staffs in Astro. Therefore, based on the finding it is showed that those three diversities are actually having relationship towards perceive of group performance for the staffs. Therefore, it at the same time this study is actually had achieved to those three objectives that been set by the researchers on in order to identify those three diversities and their relationship with perceive of group performance at their work task. Based on the finding and recommendation that been done and given by the researchers it actually can give the organization itself on how to improved the issue on the diversity workforce that been practice in the organization since it actually can effect and influence towards perceive of group performance in the organization.